Possible impacts of a 1000 km long hypothetical subglacial river valley towards Petermann Glacier in northern Greenland - C. Chambers (The Cryosphere, 2020)
Greenland basal topographic data show a segmented valley extending from Petermann Fjord into the centre of Greenland; however, the locations of radar scan lines, used to create the bedrock topography data, indicate that valley segmentation is due to data interpolation. Therefore, as a thought experiment, simulations where the valley is opened are used to investigate its effects on basal water movement and distribution. The simulations indicate that the opening of this valley can result in an uninterrupted water pathway from the interior to Petermann Fjord. Along its length, the path of the valley progresses gradually down an ice surface slope, causing a lowering of ice overburden pressure that could enable water flow along its path. The fact that the valley base appears to be relatively flat and follows a path near the interior ice divide that roughly intersects the east and west basal hydrological basins is presented as evidence that its present day form may have developed in conjunction with an overlying ice sheet. Experiments where basal melting is increased solely within the deep interior near the known large area of basal melting result in an increase in the flux of water northwards along the entire valley. The results are consistent with a long subglacial river; however, considerable uncertainty remains over aspects such as whether adequate water is available at the bed, whether water escapes from the valley or is refrozen, and over what form a hydrological conduit could take along the valley base.